KONSEP KEWENANGAN SEBAGAI LANDASAN FORMULASI HUKUMAN TINDAK PIDANA KORUPSI - Marah Halim (Islam Futura, 2014)
Although the Corruption Act has been specific, but its punishment system not constructed from its basic concept, that is the concept of authority. As a result, a lot of things that are paradoxical and contradictory in its substance; particularly in the construction of its criminal elements. This study departs from the belief that this problem will be solved if the system is reconstructed with reference to the concept of punishment authority as its "raw material". By dissecting the concept of authority with progressive fiqh approach that utilizes social sciences, and by using the technique of philosophical analysis of normative-prescriptive, came to the conclusion that the system of corruption punishment should refer to the status of legal subjects who holds the authority, not the aspect of state losses as Corruption Act at this time.